GAME EDUKASI TAJWID BERBASIS ANDROID PADA MATA KULIAH PENDIDIKAN AGAMA DI STMIK INDONESIA PADANG - Sotar Sotar; Arman Arman; Hardian Syahputra (Rang Teknik Journal, 2022)
At STMIK Indonesia Padang, especially in the subject of Religious Education, the method of learning the recitation of recitation media which is still valid today is the process of learning directly or face to face by giving materials and examples of how to read recitation recitation correctly. But in the face-to-face process or directly there are still difficulties for students to understand the recitation of recitation as a result of the large number of students and not much time and meetings for discussions about recitation. With the development of technology, the Tajwid Science Game application program is required on mobile. The design method used in this study is the waterfall method. The system will be built using the Action Script 3.0 programming language. The results of this study are to design an Android-based Tajweed educational game that will have a positive impact on students and teachers, so that the definition of the rules of reading the Qur'an can be understood clearly and easily. With the mobile-based game application, it certainly will be a solution to be taken anywhere and is very interesting for students because they can play while learning.